To multiply the polynomials \( (b + 8)(3b - 6) \), we can use the distributive property (also known as the FOIL method for binomials).
-
First, multiply the first terms: \[ b \cdot 3b = 3b^2 \]
-
Next, multiply the outer terms: \[ b \cdot -6 = -6b \]
-
Then, multiply the inner terms: \[ 8 \cdot 3b = 24b \]
-
Finally, multiply the last terms: \[ 8 \cdot -6 = -48 \]
Now, combine all of these results: \[ 3b^2 - 6b + 24b - 48 \]
Combine like terms: \[ 3b^2 + (24b - 6b) - 48 = 3b^2 + 18b - 48 \]
So, the simplified result of \((b + 8)(3b - 6)\) is: \[ \boxed{3b^2 + 18b - 48} \]